Proceedings of unconventional gas recovery - Unconventional Gas Recovery Symposium (1984 : Pittsburgh, Pennsylvania); Society of Petroleum Engineers of AIME (Dallas, Tex. : Soc. of Petroleum Engineers of AIME, 1984)
51